The role of knowledge management in improving professional relations – A field study on administrative staff in the Emirate of Makkah Al-Mukarramah Region - Midad, Ruwayna Talal (Journal of Economic, Administrative and Legal Sciences, 2023)
The current study aimed to demonstrate the role of knowledge management in improving professional relations in the Emirate of Makkah, in Jeddah. The study population consisted of all workers, administrators,), and the number of employees and workers in the emirate (742) employees on the job. A random, exploratory sample of (25) questionnaires. The Important: The Emirate of Makkah is keen to provide sources to obtain information that helps administrators and workers. The Emirate stores available data and information in a variety of ways within standards commensurate with the nature of its business. There are statistically significant differences between the average responses of the study sample, due to gender. The Recommendations: The need to adopt knowledge management as an entry point for developing and improving professional relations. Creating a motivating, encouraging and supportive culture for knowledge production and sharing. Holding periodic meetings in the various departments through which distinguished experiences and practices are presented.
Keywords: knowledge management; professional relations; Makkah